The Influence of Financial Report Quality, CEO Career Concern, and CEO Gender on Investment Efficiency with Good Governance as a Moderating Variable - Aulia, Darlin; Rochmah, Wachda Yuniar; Naya, Fannisa Egista; Ulfatun N., Tsalits Agnita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to examine the effect of Financial Report Quality, CEO Article Career Concern, and CEO Gender on Investment Efficiency with Good Governance as a Moderating variable. This research method uses Moderated Regression Analysis (MRA) with Eviews statistical tools. This study uses a sample of 680 observations of non-financial companies in Indonesia during 2022 using panel regression. The results showed that the quality of financial statements has no effect on investment efficiency. The quality of financial statements that has no effect is possible because the overinvestment scenario also has no effect. In this condition, the quality of financial statements has not been able to mitigate the occurrence of overinvestment due to the high agency level. Meanwhile, in underinvestment conditions, the quality of financial reporting has a significant positive effect, which means that the quality of financial reporting can reduce underinvestment because the quality of financial reporting can be used to attract external funds so that the company avoids underinvestment conditions. The career concern variable of the president director has no effect on investment efficiency, this is possible because in underinvestment conditions it also has no effect because most sample companies do not experience funding constraints so that the career concern of the president director does not mitigate underinvestment. Meanwhile, in overinvestment conditions, it has a positive effect. Thus, the concern of the CEO can reduce the occurrence of overinvestment. Good governance variables affect investment efficiency.